Partnered health research in Canada: a cross-sectional survey of perceptions among researchers and knowledge users involved in funded projects between 2011 and 2019 - Kathryn M. Sibley; Leah K. Crockett; Heather L. Gainforth; Ian D. Graham; Femke Hoekstra; Jeff S. Healey; Masood Khan; Sara Kreindler; Kent C. Loftsgard; Christopher B. McBride; Kelly J. Mrklas; Alexie J. Touchette (Health Research Policy and Systems)
Abstract Background Engaging knowledge users in health research is accelerating in Canada. Our objective was to examine perceptions of partnered health research among individuals involved in funded Canadian partnered health research projects between 2011 and 2019. Methods We invited 2155 recipients of 1153 funded projects to answer a questionnaire probing project characteristics and perceptions of partnered health research. We described and compared perceived effects of involving knowledge users in the project, team cohesion, capability, opportunity and motivation for working in partnership between two categories of respondents: project role [nominated principal investigators (NPIs), other researchers and knowledge users] and gender. Findings We analysed data from 589 respondents (42% NPIs, 40% other researchers and 18% knowledge users; 56% women). Among the perceived effects variables, the proportion of ratings of significant influence of involving knowledge users in the project ranged between 12% and 63%. Cohesion, capability, opportunity and motivation variables ranged between 58% and 97% agreement. There were no significant differences between respondent groups for most variables. NPIs and women rated the overall influence of involving knowledge users as significant more than other respondent groups (p < 0.001). NPIs also reported higher agreement with feeling sufficiently included in team activities, pressure to engage and partnerships enabling personal goals (all p < 0.001). Conclusions Most respondents held positive perceptions of working in partnership, although ratings of perceived effects indicated limited effects of involving knowledge users in specific research components and on project outcomes. Continued analysis of project outcomes may identify specific contexts and partnership characteristics associated with greater impact.